Interactions of gene expression, alternative splicing, and DNA methylation in determining nodule identity. (22nd June 2020) - Niyikiza, Daniel; Piya, Sarbottam; Routray, Pratyush; Miao, Long; Kim, Won‐Seok; Burch‐Smith, Tessa; Gill, Tom; Sams, Carl; Arelli, Prakash R.; Pantalone, Vince; Krishnan, Hari B.; Hewezi, Tarek
SUMMARY: Soybean nodulation is a highly controlled process that involves complex gene regulation at both transcriptional and post‐transcriptional levels. In the present study, we profiled gene expression changes, alternative splicing events, and DNA methylation patterns during nodule formation, development, and senescence. The transcriptome data uncovered key transcription patterns of nodule development that included 9669 core genes and 7302 stage‐specific genes. Alternative splicing analysis uncovered a total of 2323 genes that undergo alternative splicing events in at least one nodule developmental stage, with activation of exon skipping and repression of intron retention being the most common splicing events in nodules compared to roots. Approximately 40% of the differentially spliced genes were also differentially expressed at the same nodule developmental stage, implying a substantial association between gene expression and alternative splicing. Genome‐wide‐DNA methylation analysis revealed dynamic changes in nodule methylomes that were specific to each nodule stage, occurred in a sequence‐specific manner, and impacted the expression of 1864 genes. An attractive hypothesis raised by our data is that increased DNA methylation may contribute to the efficiency of alternative splicing. Together, our results provide intriguing insights into the associations between gene expression, alternative splicing, and DNA methylation that may shape transcriptome complexity and proteome specificity in developing soybean nodules. Significance Statement: The identity of nitrogen‐fixing nodules is determined through the function of a unique set of transcription factors in association with other transcriptional and post‐transcriptional regulatory mechanisms, which remain largely unknown. Profiling the transcriptome, spliceome, and methylome of developing soybean nodules revealed dynamic changes in gene expression, reprogramming of DNA methylation, and widespread of alternative splicing events that contribute to transcriptome complexity and proteome diversity. Our analyses expand current knowledge of gene regulatory mechanisms during nodulation.